2016
DOI: 10.1103/physrevd.94.094001
|View full text |Cite
|
Sign up to set email alerts
|

Two-solar-mass hybrid stars: A two model description using the Nambu–Jona-Lasinio quark model

Abstract: Hybrid stars with a quark phase described by the Nambu-Jona-Lasinio model are studied. The hadronquark model used to determine the stellar matter equation of state favors the appearance of quark matter: the coincidence of the deconfinement and chiral transitions and a low vacuum constituent quark mass. These two properties are essential to build equations of state that predict pure quark matter in the center of neutron stars. The effect of vector-isoscalar and vector-isovector terms is discussed, and it is sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 57 publications
4
72
1
Order By: Relevance
“…The recent observation of neutron stars with masses of approximately 2M ⊙ [52,53] places a strong limit on the equation of state of cold and dense matter. Studies performed including vector interactions typically lead to an increase of the calculated stellar masses [54][55][56], and it has been suggested that without these, the two-solar mass constraint cannot be satisfied. Therefore it could be interesting to study the effect of vector interactions on the Although within the present type of models the impact of compact star conditions on the behavior of dense quark matter in the absence of magnetic fields was already analyzed almost 15 years ago [37,49], we find it useful to review some issues concerning the parameter dependence of the results.…”
Section: Discussionmentioning
confidence: 99%
“…The recent observation of neutron stars with masses of approximately 2M ⊙ [52,53] places a strong limit on the equation of state of cold and dense matter. Studies performed including vector interactions typically lead to an increase of the calculated stellar masses [54][55][56], and it has been suggested that without these, the two-solar mass constraint cannot be satisfied. Therefore it could be interesting to study the effect of vector interactions on the Although within the present type of models the impact of compact star conditions on the behavior of dense quark matter in the absence of magnetic fields was already analyzed almost 15 years ago [37,49], we find it useful to review some issues concerning the parameter dependence of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of the application of this model and its improved versions include hadron phenomenology and behavior at finite temperature and/or density, modeling neutron star matter and study of the QCD phase diagram [14][15][16][17]. Understanding the phase diagram of QCD is one of the most challenging and interesting topics in modern physics.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever possible, the binodal sections are obtained. We include in the quark model a vector contribution that has proved to make the quark EoS stiffer and may have important consequences on the structure of hybrid or pure quark compact stars [33][34][35][36]. In particular, the inclusion of this term gives rise to larger star masses although with smaller quark cores in the case of hybrid stars.…”
Section: Introductionmentioning
confidence: 99%